HDR Syndrome Accompanying Type 1 Diabetes Mellitus and Hypopituitarism. (16th May 2019) - Can, Mustafa; Karakurt, Feridun; Kocabas, Muhammed; Cordan, İlker and Karakose, Melia and Kulaksızoglu, Mustafa
Abstract : HDR (Hypoparathyroidism, Deafness, and Renal Dysplasia) syndrome is an autosomal dominant disorder characterized by the triad of hypoparathyroidism, sensorineural deafness, and renal disease. Approximately 65% of patients with HDR syndrome have all three of these features, while others have different combinations of these features. We aimed to present a case with primary hypoparathyroidism, hearing loss, and nondiabetic chronic kidney disease and diagnosed as HDR syndrome while being followed up for type 1 diabetes mellitus and hypopituitarism.